Chronic pain and quality of life in elderly in times of COVID-19 pandemic (Research, Society and Development, 2022)
The general objective was to analyze chronic pain and quality of life in elderly individuals who self-reported as having chronic pain in the COVID -19 pandemic. This was a quantitative, descriptive, exploratory and cross-sectional study, with a stratified sample composed of 20 elderly individuals who self-reported chronic pain patients and who participated in the open university of maturity of the State University of Paraíba. The following research instruments were used: sociodemographic questionnaires; Whoqol-bref; Whoquol-old; Visual analog pain scales; Geriatric measurement. Data were analyzed using the SPSS statistical program (version 21.0), through analysis of frequencies and correlations. For this purpose, the t test and pearson's linear correlation were used with a significance level of p < 0.05. The presence of moderate chronic pain was identified in most elderly people, from the unidimensional pain scale (vas), being studied, also verified by the Geriatric Measurement Scale (GPM), and most also reported increased pain intensity during the period. COVID -19 pandemic. The highest averages observed using the whoquol-bref were given to the domains: psychological, environment, intimacy, sensory functioning and death and dying. When the quality of life instruments were correlated with the scales, in the bivariate analysis, the averages of general quality of life were negatively correlated with VAS and GPM, with a strong relationship between these variables, indicating that as the person's pain increases elderly, there is a decrease in the general quality of life of these people.